Roll book and weekly receipts of the 6th class form at St. Patrick's School, George Leigh St., Liverpool, - O'Brennan, Elizabeth, d. 1930 (1851)
Also includes French prose, children's drawings, mathematical sums and handwriting practice. Includes the inscriptions "Elizabeth Mary Anne Josephine Butler" and "Lizzie Butler" as well as "Maggie Nolan" and "Bessy Palmer".